Neuroinfection as a Mask of Lung Cancer: A Case Series - Beata Kuklińska; Anna Moniuszko-Malinowska; Robert Mróz; Sławomir Pancewicz; Joanna Zajkowska (Case Reports in Infectious Diseases)
Introduction. The diagnosis of lung cancer may still be difficult due to the fact that the first symptoms very often mimic symptoms of other diseases. Case Presentation. In this paper we present two cases, in which initial diagnosis of neuroinfection delayed proper diagnosis. Conclusion. Based on our experience we concluded that neurological symptoms in the area endemic for tick-borne diseases suggesting neuroinfection require careful differential diagnosis. Moreover, neurological symptoms in heavy smokers may be associated with metastases of lung cancer.